2019
DOI: 10.3390/ijerph16214112
|View full text |Cite
|
Sign up to set email alerts
|

Urban Air Pollution Particulates Suppress Human T-Cell Responses to Mycobacterium Tuberculosis

Abstract: Tuberculosis (TB) and air pollution both contribute significantly to the global burden of disease. Epidemiological studies show that exposure to household and urban air pollution increase the risk of new infections with Mycobacterium tuberculosis (M.tb) and the development of TB in persons infected with M.tb and alter treatment outcomes. There is increasing evidence that particulate matter (PM) exposure weakens protective antimycobacterial host immunity. Mechanisms by which exposure to urban PM may adversely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…In this study, we found a positive association between levels of NO 2 levels and subsequence prevalence of SARS-CoV-2 positivity in Northern Italy, though this occurred only at high levels of NO 2 . This relation is consistent with severe outdoor air pollution enhancing the spread of the SARS-CoV-2 virus, possibly by altering the immunological status and thus increasing individual susceptibility to infectious diseases (Ibironke et al, 2019;Marchini et al, 2020;Rivas-Santiago et al, 2015;Williams et al, 2011). The area of the study comprises the densest industrial, trading and agricultural zone in Italy, with an orography that favors the stagnation of pollutants.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we found a positive association between levels of NO 2 levels and subsequence prevalence of SARS-CoV-2 positivity in Northern Italy, though this occurred only at high levels of NO 2 . This relation is consistent with severe outdoor air pollution enhancing the spread of the SARS-CoV-2 virus, possibly by altering the immunological status and thus increasing individual susceptibility to infectious diseases (Ibironke et al, 2019;Marchini et al, 2020;Rivas-Santiago et al, 2015;Williams et al, 2011). The area of the study comprises the densest industrial, trading and agricultural zone in Italy, with an orography that favors the stagnation of pollutants.…”
Section: Discussionsupporting
confidence: 75%
“…Long-term exposure to air pollutant levels has been linked to chronic lung inflammation, thus possibly promoting an increased severity of COVID-19 syndrome (Shi et al, 2020). Air pollutants have also been shown to alter the immunological status and thus increasing individual susceptibility to infectious diseases (Ibironke et al, 2019;Marchini et al, 2020;Rivas-Santiago et al, 2015;Williams et al, 2011). As specifically regards trafficgenerated nitrogen dioxide, it has been shown to be associated with increased risk of rhinitis in adult population (Cesaroni et al, 2008; de Table 1 Cumulative number of total COVID-19 deaths, mortality rate (per 100,000 people) and nitrogen dioxide (NO 2 ) levels (μmol/m 2 ), before the lockdown, on March 8, March 22, and April 5 in Veneto and Emilia-Romagna regions.…”
Section: Discussionmentioning
confidence: 99%
“… 7 There is mounting evidence that PM exposure weakens protective antimycobacterial host-immunity; air pollution increases the risk of new infections with Mycobacterium tuberculosis. 33 In this perspective, there are suggestions that BCG vaccines have a protective effect on COVID-19. The BCG vaccination reduces the viremia from viral respiratory tract infections by boosting non-specific Th1 an Th17 response.…”
Section: Air Pollution: a Determinant Of Coronavirus Disease (Covid-1mentioning
confidence: 99%